Pengaruh Penambahan Carboxymethyl Cellulose Terhadap Karakteristik Bioplastik Dari Pati Ubi Nagara (Ipomoea batatas L.) - Puryati Ningsih, Erni; Ariyani, Dahlena; Sunardi, Sunardi (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
Synthesis and characterization of bioplastics from Nagara sweet potatoes (Ipomoea batatas L) starch with carboxymethyl cellulose (CMC) as a filler has been conducted. The purpose of this study was to evaluate the effects of CMC addition on the characteristic of bioplastics from Nagara sweet potato (Ipomoea batatas L) starch. Bioplastic synthesis was carried out by the melt intercalation method with variations in the amount of CMC 0-30% (w/w). Bioplastics were analyzed using FTIR spectrophotometer, thickness, solubility, water resistance, water vapor transmission rate, tensile strength and elongation. The values of the tensile strength of the bioplastic produced increases with increasing of CMC. The results also showed that the optimum CMC concentration in bioplastics production is 9% (w/w) with a tensile strength value 0.5281 N/mm2.